التجنيس الأدبي في النقد العربي بين الجاحظ والكلاعي ( التأسيس و التأصيل) - ريمة, حليس; مختار, ملاس (جامعة الوادي - University of Eloued, 2021)
ملخص: بالعودة إلى المدونات النقدية التراثية القديمة، نجد أن إشكالية التجنيس الأدبي في النقد العربي القديم مسألة قديمة في تاريخ الأدب العربي ونقده، تعود أولياتها إلى مرحلة التأسيس مع الجاحظ، لتكتمل بوعي تصنيفي أجناسي كمرحلة من التأصيل مع الكلاعي، تخللتها مرحلة من الشك بين من بنفي ويعدم وجودها، وبين مثبت لها، ليتم الاتفاق على غياب نظرية متكاملة للأجناس الأدبية في تراثنا العربي، مع تجلي بعض بوادرها وملامحها وإشاراتها عند أغلب النقاد العرب القدماء. Abstract: By rechecking the heritage old critical records, we find that the problematic of literary genrization in the ancient Arabic criticism is an old issue in the history and criticism of Arabic literature. Its emergences go back to the foundation stage with Al-Jahiz. To be completed withgenres’ classification as a rooting stage with Al-Kilai, during which a period of suspicion came between those who denied it and those who confirmed it. Thus, it was agreed upon the absence of an integrated theory of literary genres in our Arab heritage, despite the existence of some of its signs, features and indications that are evident to most of the ancient Arab critics.key words: word; word; word; word; word; (between 05 and 07 words).
Keywords: التجنيس، الأدب، النقد، الجاحظ، الكلاعي، التأسيس، التداول; genrization, literature, criticism, Al-Jahiz, Al-Kalai, foundation, deliberation